2015
DOI: 10.1186/s40064-015-1335-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lactobacillus salivarius alanine racemase: short-chain carboxylate-activation and the role of A131

Abstract: Many strains of lactic acid bacteria produce high concentrations of d-amino acids. Among them, Lactobacillus salivarius UCC 118 produces d-alanine at a relative concentration much greater than 50 % of the total d, l-alanine (100d/d, l-alanine). We characterized the L. salivarius alanine racemase (ALR) likely responsible for this d-alanine production and found that the enzyme was activated by carboxylates, which is an unique characteristic among ALRs. In addition, alignment of the amino acid sequences of severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Results indicate that the rALRase is stable at 4–40°C. In addition, L. salivarius with ALRase had heat tolerance for 30 min at 50°C: 70% of its activity was retained, as reported by Kobayashi et al (2015). Furthermore, ALRase having Bacillus anthracis had heat tolerance, even at 60°C, at which 60% of its activity remained (Kanodia et al, 2009).…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Results indicate that the rALRase is stable at 4–40°C. In addition, L. salivarius with ALRase had heat tolerance for 30 min at 50°C: 70% of its activity was retained, as reported by Kobayashi et al (2015). Furthermore, ALRase having Bacillus anthracis had heat tolerance, even at 60°C, at which 60% of its activity remained (Kanodia et al, 2009).…”
Section: Resultssupporting
confidence: 63%
“…and Geobacillus spp. : 129th lysine in amino acid residue (K129), 138th arginine in amino acid residue (R138), 314th methionine in amino acid residue (M314), and 315th aspartic acid in amino acid residue (D315) (Kanodia et al, 2009; Kobayashi et al, 2015; Morollo et al, 1999). Kobayashi et al (2015) reported histidine and leucine in approximately the 130th amino acid residue as H129 and L130 in ALRmase in Lactobacillus salivarius , and H127 and L128 in that of the Bacillus spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the relationship between d-amino acids and lactic acid bacteria should be further studied. Research into the enzymatic properties of these racemases has revealed a unique characteristic of AlaR from Lactobacillus salivarius UCC118 (LsAlaR) [49]. The presence of short-chain carboxylates, such as acetate and propionate, stabilizes and activates the LsAlaR, and these carboxylates generally inhibit the racemization activity of AlaR as substrate analogs [50].…”
Section: D-amino-acid-metabolizing Enzymes In Lactic Acid Bacteriamentioning
confidence: 99%
“…A lysine residue at position 129 in ALR from Geobacillus stearothermophilus is conserved in many well-studied ALRs, whereas it is replaced with alanine in ALR from Ligilactobacillus salivarius. Previous studies indicate that short-chain carboxylates inhibit ALRs from G. stearothermophilus and Bacillus anthracis by acting as substrate analogues, whereas L. salivarius ALR is activated by carboxylates, such as acetate and propionate [10][11][12]. Replacement of this alanine with lysine at position 129 in L. salivarius ALR prevents the enzyme from being activated by the carboxylates, indicating that this residue plays a crucial role in activation/inhibition, although the associated mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%